Pandangan Mahasiswa Terhadap Catcalling dan Peran Satgas PPKPT dalam Pencegahan serta Penanganannya di Universitas Negeri Medan - Martua Felix Jonatan Simanullang; Arief Wahyudi; Dewi Pika Lbn Batu; Majda El Muhtaj; Parlaungan G Siahaan (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze student perceptions of catcalling and examine the role of the Higher Education Violence Prevention and Handling Task Force (PPKPT Task Force) in preventing and handling such conduct at Universitas Negeri Medan. This research employed an empirical normative legal method with a qualitative descriptive approach. The findings indicate that most students understand catcalling as a form of verbal sexual harassment, although some still normalize it as a joke. The PPKPT Task Force has carried out preventive measures through socialization and education programs, while handling efforts include reporting mechanisms, investigations, victim assistance and recommendations to the university. Obstacles include low reporting rates, limited outreach, lack of student awareness, and the absence of comprehensive internal regulations. Strengthening legal awareness and institutional capacity is therefore necessary to create a safer campus environment.